Service marketing and its influence on consumer loyalty in a B2B company, Piura, Piura, 2022 - Padilla-Santos, Solanyi; Fernández-Bedoya, Víctor Hugo (LACCEI, 2023)
The objective of this research was to determine the influence of service marketing on the loyalty (and its dimensions: information, consumers, communication, consumer experience and incentives and privileges) of consumers in a B2B company, Piura, 2022. The methodology had a qualitative approach, basic type, exploratory level, non-experimental design. In addition, an interview guide was applied as an instrument. The participants of the study were 10 workers of the B2B company. The technique applied was the interview. The instrument (interview guide) consisted of 22 items. The results showed that service marketing does have an influence on consumer loyalty in a B2B company, Piura. In addition, it was shown that it is essential to apply 5 dimensions: communication with customers, qualified personnel, experience in carrying out quality projects and services, personalized work adapted to the company’s segment, meeting agreed deadlines, guaranteed work and payment facilities. Finally, a discussion with background and final conclusions was issued.